An Analysis of Economic Policies Implemented by Prophet Muhammad during His Governance in Madinah: A Comparative Study with Capitalist and Socialist Economic Systems - Haisy, Noorwahidah (Universitas Muhammadiyah Jember, 2023)
This study aims to examine and analyze the economic policies implemented by Prophet Muhammad during his governance in Madinah, and to compare them with capitalist and socialist economic systems. Through an analysis of historical sources and existing research on Islamic economics, capitalism, and socialism, this study aims to shed light on the distinct characteristics of Prophet Muhammad's economic policies. The research focuses on seven crucial aspects, including the market mechanism, prohibition of interest, uncertain transactions, hoarding and monopoly, and more. By uncovering these aspects, the study reveals the unique principles of Islamic economics, which prioritize ethical and moral considerations in economic transactions and reject the notion of interest. Additionally, it highlights the Prophet's implementation of a market system that fosters free competition, cooperation, and equitable exchange, while discouraging monopolistic practices. By presenting these findings, the study contributes to a better understanding of the disparities between Prophet Muhammad's economic policies and the frameworks of capitalism and socialism.